Management and organization : a critical text - Linstead, Stephen, 1952-; Fulop, Liz.; Lilley, Simon (Basingstoke : Palgrave MacMillan, 2009)
This text seeks to respond to demand for a more critical look at organizational behaviour whilst still being accessible for undergraduates, MBA students and specialist masters students. It also anchors the discipline firmly within a global context.
Previous ed.: 2004.
Includes bibliographical references and index.
Keywords: Management; Organization; Management -- Australia